Polyvinylchloride-derived N, S co-doped carbon as an efficient sulfur host for high-performance Li–S batteries. Issue 66 (12th November 2018) - Hu, Cejun; Chang, Yingna; Chen, Ruida; Yang, Jijin; Xie, Tianhui; Chang, Zheng; Zhang, Guoxin; Liu, Wen; Sun, Xiaoming
Abstract : The intrinsic polysulfide shuttle in lithium–sulfur (Li–S) batteries have significantly limited their practical applications. Abstract : The intrinsic polysulfide shuttle in lithium–sulfur (Li–S) batteries have significantly limited their practical applications. Conductive carbon materials with heteroatom doping and rich porosity is the most common strategy for the effective prevention of polysulfide shuttle, but are usually obtained with high costs and tedious procedures. Herein, we managed to obtain highly porous N, S-codoped carbon materials (NS-C) through treating waste plastic of polyvinylchloride (PVC) with KOH. The resulting NS-C was revealed to be highly efficient hosts for sulfur cathode, achieving large reversible capacities of 1205 mA h g −1 and 836 mA h g −1 at 0.1C and 1.0C, respectively, and remaining at 550 mA h g −1 after 500 cycles at 1C rate, showing an outstanding cycling stability. The significantly enhanced cycling performance was mainly ascribed to both the hierarchically porous structure and heavy N, S co-dopants, which respectively provided physical blocks and chemical affinity for the efficient immobilization of intermediate lithium polysulfides. The results provide an effective paradigm in the surface chemistry and sulfur cathode materials design for high-performance Li–S batteries and a new application for recycled plastic waste.